2012
DOI: 10.1371/journal.pone.0032092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Local Adaptation in Lunar and Diurnal Emergence Times of the Marine Midge Clunio marinus (Chironomidae, Diptera)

Abstract: Circadian rhythms pre-adapt the physiology of most organisms to predictable daily changes in the environment. Some marine organisms also show endogenous circalunar rhythms. The genetic basis of the circalunar clock and its interaction with the circadian clock is unknown. Both clocks can be studied in the marine midge Clunio marinus (Chironomidae, Diptera), as different populations have different local adaptations in their lunar and diurnal rhythms of adult emergence, which can be analyzed by crossing experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
4
33
0
Order By: Relevance
“…1B) can be now considered as having the smallest genome size of any known insect, with a C-value of 0.07 pg DNA, corresponding roughly to 68 Mb. This value is congruent with the genome size of a related species, Clunio marinus, which was estimated once to 95 Mb and more recently to 87.2 Mb (Kaiser and Heckel, 2012;Tobias S. Kaiser, personal communication).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1B) can be now considered as having the smallest genome size of any known insect, with a C-value of 0.07 pg DNA, corresponding roughly to 68 Mb. This value is congruent with the genome size of a related species, Clunio marinus, which was estimated once to 95 Mb and more recently to 87.2 Mb (Kaiser and Heckel, 2012;Tobias S. Kaiser, personal communication).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, small genome sizes should constitute an advantage for chironomid species rapidly developing in temporary environments. Chironomids from the genus Clunio can develop into temporary tide pools and also show synchronized emergence of the adults in relation to the moon cycle and during the short window of the low tide (Kaiser and Heckel, 2012). A high developmental rate should be needed to achieve this.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping of clock genes and light receptors identified ciliary opsin 2 as a candidate to be involved in both lunar and diurnal timing; cryptochrome 1 (cry1 ¼ 'Insect type' cryptochrome; main photoreceptor of the circadian clock in D. melanogaster) as a candidate gene for lunar timing; and two timeless (tim2, tim3) genes as candidate genes for diurnal timing [93]. tim2 is also called timeout and is involved in chromosome stability and light entrainment of the circadian clock in D. melanogaster [94].…”
Section: (I) Invertebratesmentioning
confidence: 99%
“…tim2 is also called timeout and is involved in chromosome stability and light entrainment of the circadian clock in D. melanogaster [94]. The function of tim3 is still unknown, but it has sequence similarities to tim2 and is also present in mosquitoes as Aedes aegypti and Culex quinquefasciatus [93]. The photoreceptor responsible for moonlight detection is most probably located in the larval ocelli [95].…”
Section: (I) Invertebratesmentioning
confidence: 99%
“…In Clunio , experimental studies have identified functional and pigment changes in the larval ocelli 12 together with a photoreceptor pigment (ciliary opsin 2) and a known insect circadian clock gene Cryptochrome1 that are now thought to be associated with the lunar rhythm 13 . Most recently the characterization of the Clunio genome has identified orthologues for the circadian clock genes but these do not yet explain the lunar mechanism 14 .…”
Section: Introductionmentioning
confidence: 99%